PENGARUH PEMUPUKAN DAN VEGETASI TERHADAP KEBERADAAN JAMUR TANAH DI LAHAN BEKAS PENAMBANGAN EMAS YANG DIREKLAMASI PADA DAERAH CIMANGGU DAN BOJONG PARI JAMPANG SUKABUMI - Titin Yulinaeri; Suciatmih Suciatmih; Nandang Suharna (The East Java Biological Society, 2001)
In order to know the effect of vegetation and fertilizer on the occurrence of soil fungi, a study was conducted in reclamated gold mining land both in Cimanggu and Bojong Pari, Jampang, Sukabumi. Soil fungi were isolated by dilution plate method, using a â€œtauge sucrose agarâ€? medium with 50 ppm antibiotic and incubated at room temperature for 2-3 days. Fungi identification follows Domsch et al (1980), Samson et al (1981), and Barnet (1969).The effect of vegetation and fertilizer on the composition of soil fungi in reclamated land both Cimanggu and Bojong Pari were not quite different. Aspergillys, Eupenicillium, and Pennicillium maybe dominant fungi in these areas. These fungi were probably involved in reclamation of land. To obtain faster reclamation process, the fungi are better involved as one of introduced microorganism besides Rhizobium and Mychorizal fungi or mixed inoculants. Besides election of suitable flora and fauna, soil fungi are expected to be able recover degraded land into original ecosystem.